The study of mechanical properties and fracture evolution of coal-rock masses under hard roof-soft floor conditions - Jiajun Li; Yin Zhang; Chenchen Yang; Jiaqi Liu; Yu Zhou; Chunlin Li (Scientific Reports)
Abstract As the depth of coal mining in China continues to increase, the fracturing of coal rock masses has an increasingly complex impact on the surrounding rock roadways. The majority of the mine’s roadways run through coal rock masses with hard roofs and soft bottoms, which typically exhibit complex dynamic behaviour. To further research the mechanical behaviour and fracture evolution of coal rock masses under hard-roof and soft-floor conditions, the study is based on the majority of working faces in a mine, which have hard roofs and soft floors. Uniaxial compression tests were utilized to study the mechanical properties of coal rock masses under hard-roof and soft-floor circumstances, using acoustic emission monitoring, whole-process imaging technologies, and fractal dimension analysis. The experimental results are as follows: The uniaxial compressive strength of the coal rock mass is significantly higher than that of its weakest component. The results of the experiment are as follows: The uniaxial compressive strength of coal rock mass is significantly higher than that of its weakest component. Samples with different soft rock strengths exhibited dissipated energy greater than the accumulated energy before the stress maximum, accompanied by volume expansion and the formation of shear surfaces. Samples with higher soft rock strengths tend to exhibit brittle failure, while weaker samples show stress-softening behaviour. Internal fracture complexity varies amongst samples with varying soft rock strengths. A fractal study of the acoustic emission parameters was carried out utilizing MATLAB programming. The fractal analysis results show that acoustic emission ringing counts and energy time series of coal rock masses under hard-roof and soft-floor settings have good fractal properties. The fractal analysis results show that acoustic emission ringing counts and energy time series of coal rock masses under hard-roof and soft-floor settings have good fractal characteristics. Acoustic emission ringing counts tend to have a larger correlation dimension than acoustic emission energy. However, while the sample is fracturing on a vast scale, the ringing count correlation dimension fluctuates very little. The correlation dimension distribution of samples with lower strength is more concentrated after the stress maximum, implying that the deformation and fracturing of the floor rock in highways under hard-roof and soft-floor circumstances are more complex. Both the correlation dimension D of acoustic emission ringing counts and energy indicate a continuous fall before peak stress, which can be used to anticipate coal rock mass fracture. This study, based on the mechanical behaviour and fracture evolution of coal rock masses under hard-roof and soft-floor conditions, provides a foundation for disaster avoidance by controlling the stability and structural deformation of floor rock in hard-roof and soft-floor highways.